2018
DOI: 10.21307/pjm-2018-061
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology and Drug Resistance of Pathogens in Patients Hospitalized at the Nephrology Department in the South of Poland

Abstract: A b s t r a c t A retrospective study was conducted among 498 patients with urinary tract infections (UTI) referred to our department from January 2013 to December 2015. This study was performed to evaluate the etiology of UTI and the antibiotic susceptibility profile of Escherichia coli (E. coli) as the main etiological factor in different age groups. Urine samples were examined using standard microbiological methods. Three hundred sixty-three samples (72.9%) were identified as E. coli, of which 29 (8.0%) can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 36 publications
9
16
0
Order By: Relevance
“…Multi-drug resistance was much higher in CA-UTI in comparison with Com-UTI. The finding is similar to the study done by Bardoloi et al in Kerala, India26 and Michno et al in Poland 31. The result suggests that catheterization increases the degree of drug resistance in bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…Multi-drug resistance was much higher in CA-UTI in comparison with Com-UTI. The finding is similar to the study done by Bardoloi et al in Kerala, India26 and Michno et al in Poland 31. The result suggests that catheterization increases the degree of drug resistance in bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, a high percentage of K. pneumoniae (81.0%) and P. mirabilis (83.3%) showed resistance to ciprofloxacin. On the other hand, among E. coli isolates, a lower percentage (28.6%) was resistant to this antibiotic, which is in line with the results of earlier study conducted in Poland, in which resistance to fluoroquinolones was found in about 30% of E. coli [ 33 ]. Levels of resistance to aminoglycosides (amikacin—9.7% and gentamicin—24.6%) of E. coli in our study was similar to that obtained in Turkey, but in our study, the percentage of K. pneumoniae and P. mirabilis resistant to gentamicin was lower (19.0% and 40.0%, respectively) than in Turkey (41.6% and 50%, respectively) [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
“…MDR, XDR and MRSA and VRE were noted in higher numbers in case of catheter aspirated urine as compared to clean catch and nappy pad method. Several studies have suggested that isolates obtained from catheterized patient are highly resistant [42, 43]. Previous hospitalization, long-term broad spectrum antimicrobial therapy, co-morbidity, frequent instrumentation, cross transmission of pathogens in catheterized patients might explain the higher antimicrobial resistance [44].…”
Section: Discussionmentioning
confidence: 99%